Anti‐influenza virus effects of cocoa. (27th April 2015) - Kamei, Masanori; Nishimura, Hiroshi; Takahashi, Toshio; Takahashi, Nobuaki; Inokuchi, Koichi; Mato, Takashi; Takahashi, Kazuo
Abstract: BACKGROUND: Cocoa contains biologically active ingredients that have broad‐spectrum antimicrobial activity, which includes an inhibitory effect on influenza virus infection. RESULTS: A cocoa extract (CE) was prepared by treating defatted cocoa powder with boiling water. The extract demonstrated dose‐dependent inhibition of infection in Madin–Darby canine kidney (MDCK) cells infected with human influenza virus A (H1N1, H3N2), human influenza virus B and avian influenza viruses (H5N1, H5N9). CE inhibited viral adsorption to MDCK cells. Animal experiments showed that CE significantly improved survival in mice after intra‐nasal administration of a lethal dose of influenza virus. In human intervention trials, participants were allocated to two groups, one in which the participants ingested cocoa for 3 weeks before and after vaccination against A(H1N1)pdm2009 influenza virus and another in which the participants did not ingest cocoa. Neutralizing antibody titers against A(H1N1)pdm2009 influenza virus increased significantly in both groups; however, the extent of the increase was not significantly different between the two groups. Although natural killer cell activity was also elevated in both groups, the increase was more substantial in the cocoa intake group. CONCLUSION: Drinking cocoa activates natural immunity and enhances vaccination‐induced immune response, providing stronger protection against influenza virus infection and disease onset. © 2015 Society of Chemical Industry